Comparative Contents of Minerals and Dietary Fibers in Several Tropical Seaweeds - Joko Santoso; Yumiko Yoshie Stark; Takeshi Suzuki (Jurnal Pengolahan Hasil Perikanan Indonesia, 2006)
Nine species of Indonesian green, brown and red seaweeds were used in this experiment to study the distribution and contents of minerals and dietary fibers. The contents of macro and micro minerals were detected by atomic absorption spectrophotometer and inductively coupled argon plasma emission spectrometer, respectively; whereas dietary fibers were determined according to modified enzymaticgravimetric method. The contents of macro mineral were dominated by Ca, K, Na and Mg, with values range were 11.95 – 28.31, 0.30 – 27.92, 0.66 – 25.74, 2.31 – 21.52 mg/g dry weight, respectively; whereas microminerals Cu, Fe and Zn were found in low concentration. The highest and smallest content of soluble dietary fiber were found in Kappaphycus alvarezii and Halimeda macroloba, respectively. K. alvarezii also had the highest content of total dietary fiber and percent soluble dietary fiber against total dietary fiber, whereas Ulva reticulata had highest content of insoluble dietary fiber.Keywords: dietary fiber, Indonesia, mineral, seaweed